2013
DOI: 10.1089/met.2012.0102
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of Parathyroid Hormone to Vitamin D Is a Determinant of Cardiovascular Risk and Insulin Sensitivity in Adolescent Girls

Abstract: Background: Vitamin D insufficiency and higher testosterone are common in obese girls and may adversely affect glucose homeostasis and cardiovascular risk. Data are conflicting regarding the impact of parathyroid hormone (PTH) on these factors. Our objective was to determine associations of 25-hydroxyvitamin D (25-OHD), PTH, and testosterone with measures of glucose homeostasis and cardiovascular risk in adolescent girls after controlling for regional adiposity, with the hypothesis that lower 25-OHD, a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Previous studies have suggested an association of integrated assessment of vitamin D/PTH with glucose metabolism (41,42). Specifically, in a cross-sectional analysis evaluating 15 obese girls and 15 matched control subjects, Stanley et al (41) demonstrated that the ratio of PTH to vitamin D was associated with insulin sensitivity and hsCRP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested an association of integrated assessment of vitamin D/PTH with glucose metabolism (41,42). Specifically, in a cross-sectional analysis evaluating 15 obese girls and 15 matched control subjects, Stanley et al (41) demonstrated that the ratio of PTH to vitamin D was associated with insulin sensitivity and hsCRP.…”
Section: Discussionmentioning
confidence: 99%
“…OH)D in monitoring of maternal vitamin D status, although further research is needed to clarify the validity and utility of free 25(OH)D in reflecting tissue-specific activities or overall status of vitamin D. Third, parathyroid hormone (PTH), known for its synergistic role with vitamin D endocrine system,31 was not measured. Emerging evidence has also suggested the potential effects of an interaction between vitamin D and PTH on glucose metabolism 47,48. Lastly, because of a lack of information on determinants of vitamin D levels such as sun exposure or outdoor activities, residual confounding from them cannot be completely ruled out.In conclusion, our results suggest that early-pregnancy vitamin Ddeficiency may increase the risk of developing GDM in pregnant women.…”
mentioning
confidence: 99%
“…These possibilities have prompted the inclusion of PTH measurements in clinical investigations of vitamin D status in patients with dysmetabolism (11).…”
mentioning
confidence: 99%